THEORETICAL FOUNDATIONS OF USING LOGISTICS SERVICES TO ENHANCE THE EXPORT POTENTIAL OF UZBEKISTAN - Alimova , Munisa Yulchiyevna; Toshpulatov, Asilbek Bakhtiyarovich (THE INNOVATION ECONOMY, 2026)
This article examines the theoretical foundations and practical mechanisms of using logistics services to enhance the export potential of Uzbekistan. The study analyzes the role of logistics services in the national economy, their importance in export processes, as well as the impact of transport, warehousing, customs, and information logistics systems on improving efficiency. The research findings contribute to the development of scientific and practical conclusions and recommendations aimed at promoting export-oriented production, modernizing logistics infrastructure, and ensuring the effective use of international logistics corridors.